Nitrogen Mineralization from Animal Manures and Its Relation to Organic N Fractions - Ling-ling LI; Shu-tian LI (Journal of Integrative Agriculture)
Laboratory aerobic incubation was conducted for 161 d to study N mineralization and the changes of organic N fractions of nine different manures (3 chicken manures, 3 pig manures and 3 cattle manures) from different farms/locations. Results indicated that significant (P<0.01 or P<0.001) difference existed in N mineralization between manures. The rapid N mineralization in manures occurred during 56 to 84 d of incubation. First order exponential model can be used to describe N mineralization from chicken manures and pig manures, while quadratic equation can predict mineralization of organic N from cattle manures. An average of 21, 19 and 13% added organic N from chicken manure, pig manure and cattle manure was mineralized during 161 d of incubation. Amino acid-N was the main source of N mineralization. The changes of amino acid-N together with ammonium N could explain significantly 97 and 96% of the variation in mineralized N from manured soils and manures. Amino acid-N and ammonium N are two main N fractions in determining N mineralization potential from manures. Amino acid-N contributed more to the mineralized N than ammonium N.